Frequency of Cognitive Impairment Among Malaysian Elderly Patients Following First Ischaemic Stroke—A Case Control Study - Mohamed Fuad, Zeena; Mahadzir, Hazlina; Syed Zakaria, Syed Zulkifli; Mohamed Ibrahim, Norlinah (Frontiers in Public Health, 2020)
Background: Stroke is highly prevalent globally and is an important cause of cognitive impairment and dementia. Aims: We determined the frequency of post-stroke cognitive impairment (PSCI) at 1, 3 and 6 months among patients with first clinical ischemic stroke compared to risk and age-matched controls. Methods: This study involved 32 cases and 32 controls, and was conducted over 6 months. Cases were inpatients aged >60 with first clinical ischemic stroke. Controls were age-matched subjects without prior stroke. Montreal Cognitive Assessment (MoCA) was performed in all patients at 1 month, 3 month and 6 month post stroke. A MoCA score of < 26 was used for mild PSCI and <22 for moderate PSCI (post stroke dementia). Results: Post-stroke dementia was detected in 12 patients (37.5%) at 1st month, in 13 (40.6%) at 3rd month and 15 (48.4%) at 6th months. Mild PSCI was present in 7 patients (21.6%) at 1 month, 16 patients (50%) at 3 months and 15 patients (48%) at 6 months. The odds ratio (OR) for post-stroke dementia was 3.2 (95%CI 0.98-10.68; p=0.05) at 1 month; 3.69(95% CI 1.13-12.11; p=0.031) at 3 months, and 4.88 (95% CI 1.49-15.99; p=0.009) at 6 months. Years of education was an independent predictor for dementia (OR 0.60; p=0.046). The OR for post-stroke dementia at 6th month was 7.23 with education level adjusted (95%CI 1.46-35.86, p=0.015). Conclusion: The frequency of PSCI was high as early as 1 month after stroke. Stroke alone conferred a 7.2 times risk for post-stroke dementia compared to controls.